(untitled) (Journal of Asian Development Studies, 2025)
This study examines post-colonialism analysis in "The Year of Sound and Heat" (2022), written by a Pakistani writer, Zain Saeed. For the critical analysis of discovering the main characteristics of post-colonialism, this research draws on the theory of post-colonialism proposed by Edward Said, in his book "Orientalism" (1977). This study explores significant post-colonialism characteristics, including marginalisation, identity, multiculturalism, hybridity, and migration. These elements of post-colonialism are evident through the depressed situations, circumstances, and characters of Jogi, Natasha, Billoo, and Disco. The analysis was conducted through textual analysis of a non-empirical research design, followed by close reading. The study concludes that the essentials of post-colonialism, including marginalisation, identity, multiculturalism, hybridity and migration in "The Year of Sound and Heart", are the fundamentals of the book and an in depth understanding of postcolonial literature that would facilitate its readers, scholars and academies in the field of post-colonialism in modern Pakistani literature.